TRACE ELEMENT MOBILIZATION IN SUBDUCTED SLABS: CONSTRAINTS ON AN ECLOGITE-FACIES TRANSPORT VEIN FROM THE WESTERN TIANSHAN, NW CHINA - Xiong X.; Gao J.; John T.; Klemd R.; Huang D. (My University, 2006)
The mafic high-pressure rocks from the western Tianshan exhibit an interconnected network of eclogite-facies veins derived by prograde blueschist dehydration. They provide insight into fluid-rock interactions and element load during long-distance fluid flow under high-pressure conditions in subduction zones. Petrographic evidence indicates that the infiltration of external fluids produces the transport vein, while continuous channeled flow of fluids leads to the leaching of the blueschist host. The almost twice as high Li-concentration of the vein and the blueschist alteration zone in comparison to the blueschist host supports the assumption of an external origin for the fluids. These fluids trigger the eclogitization of the blueschist host forming the blueschist alteration zone. The low in trace element vein-forming fluid causes a strong leaching of all trace elements in those parts of the host the passing fluid reacted with. In this process 53%-81% of the trace elements are mobilized which coincides with a loss of the large-ion-lithophile-and light-rare-earth-elements (LILE and LREE), almost twice as high than the loss of the heavy-rare-earth- and high-field-strength-elements (HREE and HFSE).
Keywords: ELEMENT LEACHING; HIGH-PRESSURE VEIN; SUBDUCTION ZONE; TRACE ELEMENT MOBILITY; WESTERN TIANSHAN